Los grabados de José Sabogal en libros y revistas: aportes al diseño gráfico peruano a inicios del siglo XX - Valenzuela Suárez, Claudia Catherine (2022)
Sabogal, along with other intellectuals, reflected on their concerns about the complementarity of the text with the image and the artifact that contained them. It was an incipient discipline, without a name. However, it was a cultural phenomenon that combined knowledge, aesthetics and literature, and transformed magazines and illustrated books into objects of symbolic and sociocultural value. These artefacts of the past are now invaluable and are considered pieces of historical value that allow us to build a genealogy of the design discipline prior to its institutionalization around 1960. The artistic and graphic context of the 1920s and 1930s was a laboratory for experimentation in graphic illustration and xylography, which consolidated the concept of the graphic image.